THE EFFECTIVENESS OF USING MIND MAPPING AS A LEARNING MODEL TO IMPROVE THE STUDENTS’ ENGLISH VOCABULARY - Helmi (Pahlawan, 2020)
The purpose of this study was to examine the comparison between the vocabulary mastery of students who were taught using mind mapping techniques and students who were not taught using these techniques. Based on the results of preliminary observations and interviews with English teachers at local schools, there were several obstacles experienced by students in learning English. The main problem is the lack of mastery of English vocabulary that is owned by students so that they have difficulty communicating using English both spoken and written. Based on this problem, the researcher formulated the problem in this study, namely, how much influence is the mind mapping learning model to improve the English vocabulary of students in class VII at SMPN 35 Banjarmasin City. In this study, researchers are the main actors in applying the mind mapping learning model to the learning process in the classroom.This research will use quasi experimental research. The population of this study were all of the seventh grade students of SMPN 35 Banjarmasin City. The author will take a sample using purposive random sampling in which students are divided into two groups. The research instrument that will be used to collect data in this study is a test. The test results are the scores of students from the experimental and control groups. The data of the research were then analyzed through paired sample t-test after normally test. Researchers used the SPSS version 21 application. Based on the findings of this research, mind mapping technique cannot give significance influence to the students’ vocabulary mastery because significance value of wilcoxon analysis was bigger than 0,05. So the alternative hypothesis was rejected and null hypothesis is accepted. it can be concluded that mind mapping technique is not good learning model to apply in teaching English for junior high school.